Perturbation theory for operational quantum non-Markovianity - Bonifacio, Mariano; Budini, Adrián Adolfo (Taylor & Francis, 2020)
Fil: Bonifacio, Mariano Comisión Nacional de Energía Atómica. Instituto Balseiro; Universidad Nacional de Cuyo, Argentina